Common Fixed Point Results for Generalized αsp Contractive Mappings and Applications - Kastriot Zoto; Ilir Vardhami (Journal of Function Spaces)
A class of g-αsp-admissible mappings and general type g-αsp contraction mappings on b-metric-like space are defined. Some fixed point results dealing with such a class of contractions are obtained. The generalized contractions considered in this work cover and unify many particular types of contractions. Finally, we present application to the existence of solutions for a system of integral equations by means of b-metric-like spaces.